Recent Advances in Anti-Tuberculosis Drug Discovery Based on Hydrazide-Hydrazone and Thiadiazole Derivatives Targeting InhA - Yoanna Teneva; Rumyana Simeonova; Violeta Valcheva; Violina T. Angelova (MDPI AG, 2023)
Tuberculosis is an extremely serious problem of global public health. Its incidence is worsened by the presence of multidrug-resistant (MDR) strains of Mycobacterium tuberculosis. More serious forms of drug resistance have been observed in recent years. Therefore, the discovery and/or synthesis of new potent and less toxic anti-tubercular compounds is very critical, especially having in mind the consequences and the delays in treatment caused by the COVID-19 pandemic. Enoyl-acyl carrier protein reductase (InhA) is an important enzyme involved in the biosynthesis of mycolic acid, a major component of the M. tuberculosis cell wall. At the same time, it is a key enzyme in the development of drug resistance, making it an important target for the discovery of new antimycobacterial agents. Many different chemical scaffolds, including hydrazide hydrazones and thiadiazoles, have been evaluated for their InhA inhibitory activity. The aim of this review is to evaluate recently described hydrazide-hydrazone- and thiadiazole-containing derivatives that inhibit InhA activity, resulting in antimycobacterial effects. In addition, a brief review of the mechanisms of action of currently available anti-tuberculosis drugs is provided, including recently approved agents and molecules in clinical trials.